Time is the enemy: Negative symptoms are related to even slight differences in the duration of untreated psychosis - Slováková, Andrea; Kúdelka, Jan; Škoch, Antonín; Jakob, Lea; Fialová, Markéta; Fürstová, Petra; Bakštein, Eduard; Bankovská Motlová, Lucie; Knytl, Pavel; Španiel, Filip (Comprehensive psychiatry, 2024)
BACKGROUND: Negative symptoms (NS) represent a detrimental symptomatic domain in schizophrenia affecting social and occupational outcomes. AIMS: We aimed to identify factors from the baseline visit (V1) - with a mean illness duration of 0.47 years (SD = 0.45) - that predict the magnitude of NS at the follow-up visit (V3), occurring 4.4 years later (mean +/- 0.45). METHOD: Using longitudinal data from 77 first-episode schizophrenia spectrum patients, we analysed eight predictors of NS severity at V3: (1) the age at disease onset, (2) age at V1, (3) sex, (4) diagnosis, (5) NS severity at V1, (6) the dose of antipsychotic medication at V3, (7) hospitalisation days before V1 and; (8) the duration of untreated psychosis /DUP/). Secondly, using a multiple linear regression model, we studied the longitudinal relationship between such identified predictors and NS severity at V3 using a multiple linear regression model. RESULTS: DUP (Pearson's r = 0.37, p = 0.001) and NS severity at V1 (Pearson's r = 0.49, p < 0.001) survived correction for multiple comparisons. The logarithmic-like relationship between DUP and NS was responsible for the initial stunning incremental contribution of DUP to the severity of NS. For DUP < 6 months, with the sharpest DUP/NS correlation, prolonging DUP by five days resulted in a measurable one-point increase in the 6-item negative symptoms PANSS domain assessed 4.9 (+/- 0.6) years after the illness onset. Prolongation of DUP to 14.7 days doubled this NS gain, whereas 39 days longer DUP tripled NS increase. CONCLUSION: The results suggest the petrification of NS during the early stages of the schizophrenia spectrum and a crucial dependence of this symptom domain on DUP. These findings are clinically significant and highlight the need for primary preventive actions.
Keywords: Multivariate Analysis; syndrom Nijmegen breakage; Nijmegen Breakage Syndrome; lidé; antipsychotika; Antipsychotic Agents; psychotické poruchy; multivariační analýza; Psychotic Disorders; Schizophrenia; schizofrenie; Humans